Vibration, acoustics and strain measurement : theory and experiments - Sujatha, C. (Cham, Switzerland : Springer : Ane Books Pvt. Ltd., 2023)
This textbook provides a comprehensive description of a variety of vibration and acoustic pickups and exciters, as well as strain gauge transducers. It is an exhaustive manual for setting up basic and involved experiments in the areas of vibration, acoustics and strain measurement (using strain gauges only).
Pre spoločné vydanie s Ane Books Pvt. Ltd. bolo dané ISBN 978-9-389-21280-8
Obsahuje bibliografie a register
Keywords: vibrácie; Vibration; akustika; akustika; tenzometre; Strain gauges; príručky; Handbooks and manuals